2022
DOI: 10.1186/s41479-022-00102-4
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for childhood pneumonia at Adama Hospital Medical College, Adama, Ethiopia: a case-control study

Abstract: Background Pneumonia is an acute respiratory infection of the lungs. A child dies of pneumonia every 39 s globally. Even though pneumonia affects children worldwide, the risk and repercussions of the disease are more prevalent in poor and middle-income nations. Despite the initiatives by the Ethiopian government, there are still numerous instances and deaths caused by childhood pneumonia. Therefore, this study aimed to identify the risk factors for pneumonia among 2–59 months-old children visit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Children from families with household income ≥ 1500 Ethiopian birr 54% less (AOR = 0.45, 95% CI, 0.017–0.120, p < 0.000) are less likely to develop pneumonia when compared with families with monthly income below 1500 Ethiopian birr. This is supported by evidence from a case–control study conducted at Adama Hospital Medical College that showed children from households with low monthly incomes were more likely to develop pneumonia 27 . Another study among under‐five children in Ethiopia also showed that poverty is significantly associated with common childhood illnesses 26 …”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Children from families with household income ≥ 1500 Ethiopian birr 54% less (AOR = 0.45, 95% CI, 0.017–0.120, p < 0.000) are less likely to develop pneumonia when compared with families with monthly income below 1500 Ethiopian birr. This is supported by evidence from a case–control study conducted at Adama Hospital Medical College that showed children from households with low monthly incomes were more likely to develop pneumonia 27 . Another study among under‐five children in Ethiopia also showed that poverty is significantly associated with common childhood illnesses 26 …”
Section: Discussionmentioning
confidence: 86%
“…This is supported by evidence from a case–control study conducted at Adama Hospital Medical College that showed children from households with low monthly incomes were more likely to develop pneumonia. 27 Another study among under‐five children in Ethiopia also showed that poverty is significantly associated with common childhood illnesses. 26 …”
Section: Discussionmentioning
confidence: 99%
“…Contradictory results were obtained in a case-control study in Adama, Ethiopia, which reported children with pneumonia whose fathers were farmers. 37 Another study in Este town and the surrounding rural kebeles in northwest Ethiopia showed that nearly three-quarters of parents were farmers who had children with pneumonia. 38 Certain occupations, such as housewives or self-employed, may be associated with lower socioeconomic status; besides, self-employed and housewives’ parents may not have access to paid sick leave or health insurance, which may lead to a delay in seeking healthcare and receiving proper treatment, poor housing conditions, and limited access to adequate nutrition.…”
Section: Resultsmentioning
confidence: 99%
“…Research by Verani et al [ 14 ] indicates that household crowding is a significant risk factor for pneumonia in well-nourished children, underscoring the role of the home environment and social interaction in the risk of pediatric pneumonia. Additionally, the lack of social interaction may be a contributing factor to the increased risk of pneumonia in only children, as suggested by research from Abebaw et al [ 15 ], which found that children from larger families had a lower risk of pneumonia, possibly due to more social interaction and microbial exposure.…”
Section: Discussionmentioning
confidence: 99%